تقييم أداء الموظفين دراسة حالة بمؤسسة موبيليس -الوادي- - محمود, طواهري; سليمان, بوفروة; عامر, برشاوة; أشرف, هاني (جامعة الوادي - University of Eloued, 2023)
"هدفت هذه الدراسة إلى دراسة تقييم أداء الموظفين ، وكان الهدف الرئيسي للدراسة بيان مدى فعالية نظام تقييم الأداء مع مؤسسة موبيليس. أجرى الباحث دراسة نظرية وتحليلية لنظم تقييم الموظفين بالمؤسسة ,وقمنا باستخدام الأسلوب التحليلي والوصفي للكشف عن مدى فعالية نظام تقييم الأداء لدى هذه المؤسسة وقد استخدمنا في ذلك برنامج التحليل الاحصائي SPSS ,حيث توصلنا إلى النتائج التالية : - تحقق أهداف وتوقعات المؤسسة في نظام تقييم أداء الموظفين - وجود تقييم أداء عالي المستوى - وجود رابط كبير بين الأداء والمكافآت - وجود نظام لتقييم تطور العاملين في المؤسسة - وجود تقييم للتعامل والتوجيه في نظام تقييم أداء الموظفين - وجود تقييم للتعامل مع الأداء الضعيف الكلمات المفتاحية: تقييم الأداء , نظام تقييم الأداء , تقييم أداء الموظفين " "This study aimed to study the performance evaluation of employees, and the main objective of the study was to demonstrate the effectiveness of the performance appraisal system with Mobilis Corporation. The researcher conducted a theoretical and analytical study of the organization's employee evaluation systems, and we used the analytical and descriptive method to reveal the effectiveness of the performance appraisal system in this organization, and we used the SPSS statistical analysis program, where we reached the following results: - Achieving the goals and expectations of the organization in the employee performance appraisal system - Having a high level performance appraisal - There is a significant link between performance and rewards - The existence of a system for evaluating the development of employees in the institution - The existence of an evaluation for dealing and guidance in the employee performance appraisal system - An evaluation to deal with poor performance "
Keywords: تقييم الأداء , نظام تقييم الأداء , تقييم أداء الموظفين; Performance appraisal, performance appraisal system, employee performance appraisal